Socrates tenured : the institutions of twenty-first-century philosophy - Frodeman, Robert; Briggle, Adam (Collective studies in knowledge and society., 2016)
This book diagnoses a crisis facing philosophy - and the humanities more broadly - and sketches a path toward institutionalizing socially engaged approaches to philosophical research.